Global Trends in Intertrochanteric Hip Fracture Research From 2001 to 2020: A Bibliometric and Visualized Study - Zhang, Ze; Qiu, Yudian; Zhang, Yawen; Zhu, Yi; Sun, Fengpo; Liu, Junchuan; Zhang, Tongyi; Wen, Liangyuan (Frontiers in Surgery, 2021)
Background: Intertrochanteric femur fractures, which are common geriatric osteoporotic fractures, have imposed a huge economic and social burden. This study clarified the global status of research on intertrochanteric fractures between 2001-2020 and predicted future research trends in this field using bibliometric and visualized studies. Methods: Publications related to intertrochanteric fractures were retrieved from the Web of Science (WoS) database. All studies were published between 2001 and 2020. Bibliometric and co-occurrence analyses were conducted using VoS viewer software. Results: In total, 2,632 studies were retrieved. The number of global publications regarding intertrochanteric fractures increased annually. The United States was the largest contributor, ranking first in total publications, citations, and the H-index. Switzerland had the highest average citation frequency among the ten countries with the highest number of publications. The journal that published the most articles regarding intertrochanteric fractures was the Injury International Journal of The Care of The Injured, with 290 articles published. This journal also ranked first in the citation frequency. MJ Parker, an author, published the most papers in the field, and the University of California research team at San Francisco contributed the most publications in this field. During the co-occurrence analysis, all keywords were divided into four clusters: internal fixation study, complication study, risk-factor study, and survival and prognosis analysis study. The internal fixation and survival and prognosis analysis studies were predicted as the next hot topics in the field of intertrochanteric fractures. Conclusions: Intertrochanteric fractures are gaining increasing research attention according to the current global trend, and the number of publications regarding intertrochanteric hip fractures will continue to increase. The United States currently publishes the most articles on intertrochanteric fractures. The number of studies related to internal fixation, survival, and prognosis analysis is increasing, suggesting that these topics may become the next research hotspots in the area of intertrochanteric fractures.